SLIP-WEAKENING AND INTERACTIVE DYNAMICS OF AN HETEROGENEOUS SEISMIC SOURCE - Senatorski P. (My University, 2001)
A theoretical 3D model of a fault region includes a slip-dependent friction, tectonic loading from the sides, and deterministic, continuous time formulation of governing equations. The model reproduces such properties of real faults as earthquake nucleation, earthquake complex rupture and nonregular recurrence. In particular, it is observed that the style of faulting changes from one event to another. Since all parameters related to the constitutive law are fixed during computer simulations, it is concluded that interactions between fault segments are responsible for such behavior. Neither the constitutive law nor fault spatial heterogeneities solely create complexity; rather it is the whole interactive dynamics of the system that determines the character of its evolution. Results are illustrated by time variations of global (i.e., related to the state of the whole fault) functions, such as energy release rate, seismic moment release rate, tectonic stresses, and local characteristics, such as driving and cohesive stresses, slip rates, slip displacements and mutual relations between them.
Keywords: EARTHQUAKE CYCLE; SLIP-DEPENDENT CONSTITUTIVE LAW; SEISMIC ENERGY; SOURCE FUNCTIONS; COMPLEX RUPTURING; FAULT STRENGTH HETEROGENEITIES